Legal advice on the Chinese compensatory fund system for oil pollution damage caused by ships from the perspective of marine environmental governance - Fu, Ben-Chao; Li, He-Ran (Frontiers in Marine Science, 2023)
The frequent occurrence of oil pollution damage caused by ships, as one of the main obstructive factors for marine environmental governance, promotes the establishment of compensation funds for oil pollution damage caused by ships around the world, for example, the Oil Spill Liability Trust Fund (OSLTF) of the United States, Ship Oil Pollution Fund (SOPF) of Canada, and the International Oil Pollution Compensation Fund (IOPC) which has been widely participated worldwide. China, as a country that suffers from marine oil pollution frequently, has put great effort into the governance of the marine environment. Especially after the proposal of the “One Belt and the One Road Initiative”, China has attached increasing significance to the relevant legislation including the compensation for oil pollution damage caused by ships. In 2012, China established its compensation fund based on domestic legal documents. The last decade has witnessed the burgeoning development of the Chinese Ship-Source Oil Pollution Compensation Fund (CSOPC) in practical and theoretical aspects, as well as several defects which impede the fund to achieve its goal of marine environmental governance. As a national fund that is independent of the IOPC, CSOPC adopts several regulations distinctive from the internationally recognized practice, for instance, not recognizing pure economic loss as part of the scope of compensation. Such uniqueness, though partly originates from practical reality in China, has resulted in glaring defects including incomplete compensation scope and inappropriate compensation measures, which have resulted in the fund does not play its due role in promoting the governance of the marine environment. Given the above problems, this paper proposes to provide several legal pieces of advice from the perspective of macro policies of improving the top-level design of the system, enhancing the oil pollution compensation ability, and promoting the internationalization process. Moreover, this paper is going to provide two potential paths of regulation innovation, namely enlarging the range of compensation and establishing the emergency fund. This paper is expected to play a positive role in improving the compensation system for oil pollution damage caused by ships in China and facilitating the governance of the marine environment.